Flexed-knee gait in children with cerebral palsy: a long-term follow-up study. (April 2018) - Church, C.; Ge, J.; Hager, S.; Haumont, T.; Lennon, N.; Niiler, T.; Hulbert, R.; Miller, F.
Abstract : Aims: The purpose of this study was to evaluate the long-term outcome of adolescents with cerebral palsy who have undergone single-event multilevel surgery for a flexed-knee gait, followed into young adulthood using 3D motion analysis. Patients and Methods: A total of 59 young adults with spastic cerebral palsy, with a mean age of 26 years (sd 3), were enrolled into the study in which their gait was compared with an evaluation that had taken place a mean of 12 years (sd 2) previously. At their visits during adolescence, the children walked with excessive flexion of the knee at initial contact and surgical or therapeutic interventions were not controlled between visits. Results: Based on the change in flexed-knee gait over approximately ten years, improvements were seen in increased Gait Deviation Index (p < 0.001) and decreased flexion of the knee at initial contact (p < 0.001). Greater popliteal angle (p < 0.001), reduced Gross Motor Function Measure section D (p = 0.006), and reduced speed of gait (p = 0.007) suggested a mild decline in function. Quality-of-life measures showed that these patients fell within normal limits compared with typical young adults in areas other than physical function. Conclusion: While some small significant changes were noted, little clinically significant change was seen in function and gait, with gross motor function maintained between adolescence and young adulthood. Cite this article: Bone Joint J 2018;100-B:549–56.